PENGARUH LATIHAN SPLIT JUMP TERHADAP POWER OTOT TUNGKAI TIM BOLA VOLI PUTRA SMA N 1 PEKANBARU - Suci Pamalo; Ramadi Ramadi; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: From the observations in the field during the training and at the time of the competition, the researchers saw that there were still shortcomings in the male volleyball team of SMA N 1 PEKANBARU, namely lack of leg muscle strength. From the initial test of 1 person out of the 9 sample people whose Leg Muscle Power test researchers entered the laboratory enough, 7 out of 9 people were included in the Less category, and 1 person from 9 samples entered the less category. This research was conducted at SMA N 1 Jl. Sultan Sayarif Kasim no.159 Pekanbaru This research will be conducted after the proposal exam is completed. Because the research uses one group, this research uses an evaluation of the Pretest-Posttest Design Group. Before design is given before giving. After the research was conducted in November 2018 until December 2018 which began from data collection to processing data which was finally made a benchmark as a discussion of the results of the research: Split training research Jumping into leg muscle power of the volleyball team of SMA N 1 Pekanbaru, this shows there are significant differences in these variables. This is evidenced by the vertical jump test of 1 sample increasing by 6cm from the Preetest result (40cm-46cm). Then there were 3 samples, increasing the increase of 5 cm from the Preetest results (38cm-43cm, 36cm-41cm, 28cm-33cm), and 5 samples, 4cm from Preetest results (35cm-39cm, 48cm-52cm, 37cm-41cm, 35cm-39cm) Key Words: Split Jump Exercise, Leg Muscle Power